Approaches to Auschwitz - Rodkey, Christopher Demuth (The journal for cultural and religious theory, 2004)
A profile of Richard L. Rubenstein and John K. Roth, Approaches to Auschwitz: The Holocaust and Its Legacy. Revised edition. Louisville, KY: Westminster John Knox, 2003. 510pp. $ 29.29 (paper).